Multiplexed modulation of behavioral choice - Palmer, Chris R. (Company of Biologists, 2014)
Stimuli in the environment, as well as internal states, influence behavioral choice. Of course, animals are often exposed to multiple external and internal factors simultaneously, which makes the ultimate determinants of behavior quite complex. We observed the behavioral responses of European leeches, Hirudo verbana, as we varied one external factor (surrounding water depth) with either another external factor (location of tactile stimulation along the body) or an internal factor (body distention following feeding). Stimulus location proved to be the primary indicator of behavioral response. In general, anterior stimulation produced shortening behavior, midbody stimulation produced local bending, and posterior stimulation usually produced either swimming or crawling but sometimes a hybrid of the two. By producing a systematically measured map of behavioral responses to body stimulation, we found wide areas of overlap between behaviors. When we varied the surrounding water depth, this map changed significantly, and a new feature – rotation of the body along its long axis prior to swimming – appeared. We found additional interactions between water depth and time since last feeding. A large blood meal initially made the animals crawl more and swim less, an effect that was attenuated as water depth increased. The behavioral map returned to its pre-feeding form after approximately 3 weeks as the leeches digested their blood meal. In summary, we found multiplexed impacts on behavioral choice, with the map of responses to tactile stimulation modified by water depth, which itself modulated the impact that feeding had on the decision to swim or crawl.